Multiwall carbon nanotube modified vinylester and vinylester - based hybrid resins - Gryshchuk. O.; Karger-Kocsis, J.; Thomann, R.; Konya, Z.; Kiricsi, I.
Purified, catalytic chemically vapor deposited multiwall carbon nanotubes (MW-CNT)were incorporated in vinylester (VE), vinylester-urethane (VEUH)and vinylester/epoxy (VE/EP)systems in up to 2 wt
Keywords: NANO-STRUCTURES; THERMOSETTING RESINS; ELECTRICAL PROPERTIES; FRACTURE TOUGHNESS; THERMOMECHANICAL